Hubungan Dukungan Spiritual dengan Tingkat Kecemasan pada Penderita Diabetes Mellitus Tipe 2 - Nadia Putri Andriyanny; Muhammad Anis Taslim; Dwi Fitriyanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Diabetes mellitus (DM) is a chronic disease in which glucose levels in the blood are high because the body cannot use enough insulin. Diabetes mellitus has increased significantly both at the world and regional levels. The high incidence of DM has an impact on physical and psychological problems in DM sufferers. One of them is the impact of DM complications and anxiety. Spiritual support is a belief in a relationship with the Almighty, the Almighty Creator and spiritual support can influence the adaptive coping of someone who experiences psychological problems, one of which is anxiety. This study aims to analyze the relationship between spiritual support and anxiety levels in people with type 2 diabetes mellitus. This research design uses a cross-sectional approach. The number of samples in this study was 71 respondents with data collection techniques using purposive sampling. The statistical test used is the Spearman rank test. The results of the research show that there is a relationship between spiritual support and the level of anxiety in type 2 diabetes mellitus sufferers at the Tlogosari Wetan Community Health Center in 2024 with a significant p value = 0.001 and a correlation coefficient r value (– 0.402). It was concluded that the strength of the relationship between spiritual support and the level of anxiety is a moderate relationship, namely in the range 0.40 - 0.599 with a negative correlation direction, which means that the higher the spiritual support, the lower the level of anxiety.